Electroencephalography as a Biomarker for Functional Recovery in Spinal Cord Injury Patients - Simis, Marcel; Doruk Camsari, Deniz; Imamura, Marta; Filippo, Thais Raquel Martins; Rubio De Souza, Daniel; Battistella, Linamara Rizzo; Fregni, Felipe (Frontiers in Human Neuroscience, 2021)
Background: Functional changes after spinal cord injury (SCI) are related to changes in cortical plasticity, which can be measure with electroencephalography (EEG) and has a potential to be used as a clinical biomarker. Method: This was a longitudinal study in which patient performed 30 sessions of robotic-assisted gait training (RAGT), 30 minutes duration, five times weekly for six weeks. Resting state EEG was recorded before and after 30-session rehabilitation therapy. To measure gait, we used the Walking Index for Spinal Cord Injury (WISCI II) Scale, 10-Meter- Walking Test (10MWT), Timed-Up-and-Go (TUG) and 6-Minute-Walking Test(6MWT). To measure balance, we used Berg Balance Scale (BBS). Results: Were included 15 patients (three women) with incomplete spinal cord injury (SCI), mean age of 35.7 (SD ±10.6) years old, with mean time since injury of 17.08 (SD ±12.05) months, AIS C or D in ASIA classification. Patients clinically improved with the rehabilitation program. High beta EEG activity in the central area had a negative correlation with gait (p=0.049; β coefficient: -0.351; adj R2: 0.23) and balance (p=0.043; β coefficient: -0.158; adj R2:0.24) measured at baseline, in a way greater high beta EEG power was related to worse clinical function. Moreover, gait improvement had a negative correlation with the change in alpha/theta ratio in the parietal area (p=0.049; β coefficient: -0.351; adj R2: 0.23) and the improvement of balance had a negative correlation with the change in alpha/theta ratio in the parietal area (p=0.043; β coefficient: -0.158; adj R2:0.24). Conclusion: Functional impairment and improvement in SCI patients may be predicted by cortical activity measured by EEG.